BILATERAL AVASCULAR NECROSIS OF FEMORAL HEAD FOLLOWING COVID-19 INFECTION: CASE SERIES - Kammar, Fakruddin Shershah; Mudgal, Chandrashekar; Ramanand, Madhuchandra; Kumar, Akash (Sanamed, 2023)
Introduction: Despite having a substantial impact on survivors' mobility and leading to morbidity, musculoskeletal involvement was the post-COVID-19 infection sequelae area that received the least attention in the literature. Reviewing the COVID-19 histories of patients who visited a tertiary health center, the research is aimed at finding an association between COVID-19 infection and avascular femoral head necrosis, a condition brought on by insufficient blood flow. Avascular necrosis of the femoral head is a condition characterized by a restricted range of motion, pain, and disturbance of gait. It is brought on by insufficient blood flow. Case reports: We discussed several examples in which COVID-19 caused individuals to develop bilateral femoral head necrosis. When COVID-19 infection is the only factor present, and corticosteroids are used to treat it, avascular necrosis of the femoral head may become more prevalent. Detecting avascular necrosis of the femoral head in its early stages, hip MRI might reduce the patient's disability and need for continuous treatment. Conclusion: Early identification and treatment of AVN patients reduce the need for surgery and the chance of disabilities.
Keywords: Avascular necrosis (AVN); sedimentation rate of erythrocytes (ESR); C-reactive proteins (CRP); White blood cells (WBC); Steroid-induced AVN femoral head (SANFH)